3D finite element modeling of sling wire rope in lifting and transport processes - Kastratović, Gordana; Vidanović, Nenad (Transport, 2015)
Paper explores some aspects of 3D modeling of ‘aircraft cable’ as mostly used sling wire rope. First, the 1×19 stainless steel core of ‘aircraft cable’ was investigated. The analysis was carried out by finite element method based computer program. The software used allowed two different types of contacts, including friction. The sling wire rope core was subjected to two different types of axial loading. The obtained results were compared with the solutions calculated from the literature (Costello 2012). Finally, using the advanced modeling techniques, the parametric 3D model of 7×19 ‘aircraft cable’ was analyzed using finite element method, in order to provide a better understanding and, hence, prediction, of the mechanical behavior of the sling wire ropes in lifting processes.First published online: 16 Oct 2013